The Influence of Professional Ethics, Independence, and the Accountants' Code of Ethics on Auditor Performance at the Palopo Inspectorate - Maharani, Putri Jingga; Syamsuddin , Sofyan; Pratiwi, Indah (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2026)
This study aims to examine the influence of professional ethics, independence, and the accountants’ code of ethics on auditor performance at the Regional Inspectorate of Palopo City. Previous studies have generally examined these ethical dimensions separately, resulting in limited understanding of their combined effects, particularly in the public sector context. This study addresses this gap by integrating these variables into a single analytical framework. This research adopts a quantitative approach using an associative method. The population consists of all auditors at the Regional Inspectorate of Palopo City, with a total sampling technique resulting in 36 respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results show that professional ethics, independence, and the accountants’ code of ethics have a positive and significant effect on auditor performance. This study contributes by providing empirical evidence on the simultaneous role of ethical factors in improving auditor performance. The findings also emphasize the importance of strengthening ethical values, independence, and professional standards to enhance audit quality and public trust.